Supply chain digitalization and resilient supply chain performance: the role of supply chain financing - NTIM SARAH OFORI (KNUST, 2024)
A thesis submitted to the department of supply chain and information s systems, kunst school of business, in partial fulfillment of the requirement for the award of the degree of msc. Business administration (logistics and supply chain management)